2018
DOI: 10.1002/elan.201800331
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Sensor with Replaceable Polyaniline‐DNA Layer for Doxorubicin Determination

Abstract: New voltammetric DNA sensor has been developed on the base of glassy carbon electrode covered with electropolymerized polyaniline with entrapped native DNA saturated with Methylene blue. The thickness and redox properties of the coating are easily regulated by the number of potential cycles and pH of the solution. Doxorubicin competes with Methylene blue for DNA binding sites and suppresses the electron transfer within the layer. The measurement of the decay of the cathodic peak current made it possible to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It was determined from the necessity to reach maximal roughness of the PANI layer and to leave a part of bare electrode for further DNA adsorption. The DNA sensors obtained with 6 cycles of potential cycling performed in the presence of DNA have been recently described either [46]. First, the amounts of DNA deposited in between the PANI layers were varied.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined from the necessity to reach maximal roughness of the PANI layer and to leave a part of bare electrode for further DNA adsorption. The DNA sensors obtained with 6 cycles of potential cycling performed in the presence of DNA have been recently described either [46]. First, the amounts of DNA deposited in between the PANI layers were varied.…”
Section: Resultsmentioning
confidence: 99%
“…Recently [25,26], we have shown that DNA could be used in a biosensor assembly as a collector of doxorubicin. Their interaction results in intercalation of the DNA helix followed by changes in its charge and volume.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behavior exerts polypyrrole, though its response to biochemical reactions with DNA is milder than that of polyaniline [22]. Appropriate DNA sensors were reported for the determination of anthracyclines [23,24,25,26], salicylates [22], isoproterenol [27], and phenothiazine drugs [18,28]. However, electroconductivity of polyaniline is observed in strongly acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of double-stranded DNA on electropolymerized Neutral red resulted in detection of 0.1 nM doxorubicin by changes in the R et values in the presence of ferricyanide ions [51]. The use of DNA entrapped in the DNA decreased the LOD to 0.01 nM [52] and finally, competitive interaction with intercalated DNA allowed record LOD of 0.6 pM [48]. The advantages of the DNA sensor proposed cover higher stability of the surface layer which retains its response to doxorubicin within three months of storage in dry conditions.…”
Section: Resultsmentioning
confidence: 99%